The Influence of the Traditional Game Kopral on the Shooting Skills of Elementary School Students - Wafa, Mahrush 'Ali Wafa; Benny, Benny Widya Priadana; Hilmy, Hilmy Aliriad (Jurnal Elementaria Edukasia, 2025)
Traditional games are forms of physical activity that can be utilized in physical education to develop students’ fundamental motor skills, such as kicking or shooting abilities in football. This study aims to examine the effect of the traditional game Kopral on shooting skills in football learning among sixth-grade students at SDN Gayam 1. The research problem originated from the students’ low accuracy in performing shooting techniques. This research applied a quantitative approach with a single-group pretest–posttest experimental design. The study involved the entire population of 20 students, employing total sampling, and the research instrument was a test measuring ball-kicking accuracy. The treatment was conducted over 12 sessions through the application of the Kopral traditional game, which trains leg muscle strength, balance, and movement coordination. The analysis results showed an increase in the average shooting score from 22.15 in the pretest to 26.40 in the posttest, indicating a 19% improvement. Analysis of normality confirmed that the data were normally distributed, and the Paired Sample t-Test produced a 2-tailed Sig. value of less than 0.05, suggesting a significant difference between the pretest and posttest outcomes. These findings demonstrate that the Kopral traditional game is effective in improving students’ ball-kicking (shooting) skills. Therefore, physical education teachers are encouraged to utilize traditional games as engaging, contextual learning alternatives rooted in local cultural values.